2019
DOI: 10.1186/s13068-018-1340-4
|View full text |Cite
|
Sign up to set email alerts
|

PLDα1-knockdown soybean seeds display higher unsaturated glycerolipid contents and seed vigor in high temperature and humidity environments

Abstract: BackgroundSoybean oil constitutes an important source of vegetable oil and biofuel. However, high temperature and humidity adversely impacts soybean seed development, yield, and quality during plant development and after harvest. Genetic improvement of soybean tolerance to stress environments is highly desirable.ResultsTransgenic soybean lines with knockdown of phospholipase Dα1 (PLDα1KD) were generated to study PLDα1′s effects on lipid metabolism and seed vigor under high temperature and humidity conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 65 publications
3
42
0
Order By: Relevance
“…These non-structural components (NSC) are non-chemically bound components of lignocellulosic biomass that can directly affect pretreatment, enzymatic hydrolysis, and fermentation yields. Previous studies reported that ash increases the buffering capacity of the biomass, which negatively affects pretreatment efficiency [ 6 8 ]. Besides, Ranatunga et al [ 9 ] reported that extractives from hardwoods can inhibit xylose fermentation by Zymomonas mobilis due to their antimicrobial properties, which directly reduces the ethanol yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-structural components (NSC) are non-chemically bound components of lignocellulosic biomass that can directly affect pretreatment, enzymatic hydrolysis, and fermentation yields. Previous studies reported that ash increases the buffering capacity of the biomass, which negatively affects pretreatment efficiency [ 6 8 ]. Besides, Ranatunga et al [ 9 ] reported that extractives from hardwoods can inhibit xylose fermentation by Zymomonas mobilis due to their antimicrobial properties, which directly reduces the ethanol yield.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass preprocessing washing has been commonly used to remove ash from low-quality feedstocks to improve thermochemical conversion processes, prevent equipment corrosion and fouling caused by ash build-up, as well as to reduce biomass buffering capacity and improve pretreatment efficiency [ 6 8 , 16 ]. Preprocessing, however, has also been proposed as a method to remove other types of NSC, such as acetic acid and extractives.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and humidity are two of the pivotal environmental factors associated with seed growth and development in field. High temperature and humidity condition can not only affect seed yield and quality, but also reduce seed vigor and storage capacity [1,2], resulting in the preharvest seed deterioration. Seed vigor is a complex property that determines the seed's potential for rapid uniform germination and subsequent growth [3].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it plays an important role in pollen tube development [5], seed germination [6], the regulation of abscisic acid (ABA) and jasmonic acid (JA) signaling [7,8] and salt stress response in Arabidopsis [9]. Furthermore, the role of PLDα1 in seed quality improvement has been recently reported in soybean, where the knockdown of PLDα enhances seed quality [10].…”
Section: Introductionmentioning
confidence: 99%